2006
DOI: 10.1007/s10495-006-5114-2
|View full text |Cite
|
Sign up to set email alerts
|

Human, insect and nematode caspases kill Saccharomyces cerevisiae independently of YCA1 and Aif1p

Abstract: This study characterised the impact of active metazoan apoptotic proteases (caspases) on Saccharomyces cerevisiae viability. Expression of active caspase-3 or caspase-8 in yeast ruptured plasma and nuclear membranes and dramatically impaired clonogenic survival, but did not damage DNA. Deletion of the proposed yeast apoptosis regulators YCA1 or Aif1p did not affect the ability of human, insect or nematode caspases to kill yeast. These data indicate that expression of active metazoan caspases causes irreversibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
1
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 37 publications
(42 reference statements)
4
24
1
4
Order By: Relevance
“…The levels of Caspase expression afforded by the ADH and TEF promoters were sufficient to achieve ‘spontaneous” activation of these over-expressed proteases, but insufficient to kill yeast or impair their growth. For Caspases-8 and 10, however, we co-expressed a small amount of the full-length (zymogen) proteins using the CYC promote (a constitutive promoter with relatively weak activity) together with a large amount of the upstream activator, FADD (an adapter protein that contains a Death Effector Domain (DED) that binds the DEDs found in the prodomains of Caspase-8 and -10 [17], because large amounts of active Caspases-8 or -10 inhibited the yeast cell growth significantly, consistent with prior reports [18], [19]. Using a ΔLEU2 yeast strain containing LEU2 and lacZ reporter genes, active Caspases were co-expressed with cleavable transcription factors containing various tetrapeptide target sequences.…”
Section: Resultssupporting
confidence: 86%
“…The levels of Caspase expression afforded by the ADH and TEF promoters were sufficient to achieve ‘spontaneous” activation of these over-expressed proteases, but insufficient to kill yeast or impair their growth. For Caspases-8 and 10, however, we co-expressed a small amount of the full-length (zymogen) proteins using the CYC promote (a constitutive promoter with relatively weak activity) together with a large amount of the upstream activator, FADD (an adapter protein that contains a Death Effector Domain (DED) that binds the DEDs found in the prodomains of Caspase-8 and -10 [17], because large amounts of active Caspases-8 or -10 inhibited the yeast cell growth significantly, consistent with prior reports [18], [19]. Using a ΔLEU2 yeast strain containing LEU2 and lacZ reporter genes, active Caspases were co-expressed with cleavable transcription factors containing various tetrapeptide target sequences.…”
Section: Resultssupporting
confidence: 86%
“…It was shown that their cytotoxic effects culminate in cell death with an apoptotic phenotype characterized by production of ROS, chromatin condensation and phosphatidylserine externalization (Figure 2). In agreement with the results obtained in the previous study on caspase-8, 66 the authors found that…”
supporting
confidence: 92%
“…The expression of active mammalian, insect and nematode caspases was shown to cause damage to yeast organelles and lead to a reduction in clonogenic survival, in a manner independent of Yca1p and Aif1p. 66 Particularly, it was found that expression of active human caspase-3 and -8 induced a disruption of cellular membranes leading to damage of the plasma membrane, loss of nuclei integrity and mitochondrial structure but without evidence of DNA damage, as revealed by a TUNEL-negative phenotype 66 ( Figure 2). Unlike what is observed in mammalian cells, the authors found that active heterologously expressed caspase-3 and -8 were unable to cleave actin, this, in spite of the fact that yeast actin retains the conserved cleavage sequence for caspase-3.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Caspase toxicity in yeast depends both on the enzyme adopting an active conformation, as well as its substrate specificity. Neither of two proteins implicated in endogenous yeast cell death pathways -YCA1 (Madeo et al, 2002) and Aif1p (Wissing et al, 2004) -is required for caspase-dependent yeast lethality (Puryer and Hawkins, 2006), implying that the toxicity reflects fortuitous proteolysis of essential proteins rather than triggering of an endogenous yeast 'apoptotic' pathway.…”
Section: Resultsmentioning
confidence: 99%